2009
DOI: 10.1007/s11060-009-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with methotrexate for primary central nervous lymphoma has single agent activity in the absence of radiotherapy: a single institution cohort

Abstract: We have retrospectively reviewed toxicities and response of a cohort of primary central nervous system lymphoma (PCNSL) patients treated with high dose parenteral methotrexate (MTX) monotherapy without whole brain radiation. From The Massachusetts General Hospital (MGH) Cancer Registry, active since 1946, we selected all immunocompetent patients with histologic and/or radiographic PCNSL diagnosed between 1980 and 2007. We identified the recipients of MTX with leucovorin rescue as sole therapy. No patient recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Cobert et al reported clinical results of patients, including the elderly, treated with an average of 11 cycles of 8 g/m 2 MTX. 4) The median OS was 7 years, with only a small percentage of patients experiencing severe toxicity. The disadvantage of this protocol is the long treatment period, which includes maintenance therapy every 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cobert et al reported clinical results of patients, including the elderly, treated with an average of 11 cycles of 8 g/m 2 MTX. 4) The median OS was 7 years, with only a small percentage of patients experiencing severe toxicity. The disadvantage of this protocol is the long treatment period, which includes maintenance therapy every 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of dosage, 1–8 g/m 2 of MTX has been adopted in various clinical trials, and 3.0 g/m 2 or more of MTX is widely acce pted. 2 4 , 6 9 , 11 , 12 , 14 , 19 , 21 30 , 32) MTX appears to be readily distributed into the cerebrospinal fluid when 3.0 g/m 2 or more of MTX is administered. 17) Furthermore, a recent trial has investigated changing subsequent doses of MTX based on the plasma concentration of MTX.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of untreated PCNSL patients is extremely poor and their median survival time is 1.5-3.3 months (9). It was previously demonstrated that the MTX-based protocols could be effective compared with HD-MTX alone, but the overall response rate is poor and the toxicity is serious (10,11). Pels et al (7) reported the results of a combination of HD-MTX, high-dose of Ara-C (HD-Ara-C), vinca-alkaloids and alkylating agents treated with PCNSL.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose methotrexate (HD-MTX) is the most effective chemotherapeutic agent for PCNSL and many studies support its use as first-line therapy (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and is recommended also by the guidelines of the European Association of Neuro-Oncology (5). By the addition of calciumfolinate 24 hours after a 3-4 hour MTX infusion it is possible to increase the MTX dose by a factor of 100, thus allowing the drug to penetrate the BBB by simple diffusion.…”
Section: Introductionmentioning
confidence: 99%